2018
DOI: 10.1002/jcb.27076
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside attenuates interleukin‐1β‐induced inflammation in human osteoarthritis chondrocytes

Abstract: Salidroside, a bioactive constituent isolated from Rhodiola rosea, has been reported to have anti‐inflammatory effects. However, the effects of salidroside on interleukin (IL)‐1β‐stimulated osteoarthritis (OA) chondrocytes remain to be elucidated. Thus, this study aimed to evaluate the anti‐inflammatory effects of salidroside on IL‐1β‐stimulated human OA chondrocytes and explore its underlying mechanisms. Our results showed that salidroside significantly inhibited the production of nitric oxide and prostagland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Our results were consistent with previous research in vitro. 20,21 Salidroside is the bioactive component of Rhodiola rosea, which has various beneficial effects on human health. Numerous studies have mentioned that Sal was involved in the treatment of many diseases, such as non-alcoholic steatohepatitis 38 and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results were consistent with previous research in vitro. 20,21 Salidroside is the bioactive component of Rhodiola rosea, which has various beneficial effects on human health. Numerous studies have mentioned that Sal was involved in the treatment of many diseases, such as non-alcoholic steatohepatitis 38 and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that Sal inhibited the production of matrix metalloproteinases induced by IL-1β in human OA chondrocytes, and had a protective effect on LPS-induced ATDC5 cell damage. 20,21 According to reports, Sal had an inhibitory effect on IL-1β-induced OA inflammation by inhibiting the activation of the NF-κB pathway in vitro. 21 Similarly, this study found that Sal reduced the number of CD4 + IL-10 + cells in OA rats and increased the number of CD4 + IL-10 + cells, thereby regulating the inflammation and immune response in OA rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides this, NO has been demonstrated to modulate COX-2 expression and prostaglandin production [ 11 ] as well as the activation of MMPs in the cartilage [ 12 ]. MMPs are well characterized enzymes involved in the degradation of the extracellular matrix (ECM) of the cartilage [ 13 , 14 ]. Among them, MMP-13 (collagenase 3) is an enzyme constitutively expressed in the chondrocyte that degrades collagenous ECM [ 15 ].…”
Section: Introductionmentioning
confidence: 99%